Crystallization of the C‐terminal domain of the bacteriophage T5 L‐shaped fibre. Issue 12 (1st December 2013) - Garcia‐Doval, Carmela; Luque, Daniel; Castón, José R.; Boulanger, Pascale; van Raaij, Mark J.
<x xml:space="preserve">Abstract</x> Tails of bacteriophage T5 (a member of the Siphoviridae family) were studied by electron microscopy. For the distal parts of the L‐shaped tail fibres, which are involved in host cell receptor binding, a low‐resolution volume was calculated. Several C‐terminal fragments of the fibre were expressed and purified. Crystals of two of them were obtained that belonged to space groups P63 and R32 and diffracted synchrotron radiation to 2.3 and 2.9 Å resolution, respectively. A single‐wavelength anomalous dispersion data set to 2.5 Å resolution was also collected from a selenomethionine‐derivatized crystal of one of the fragments, which belonged to space group C2.